Efisiensi Baitul Māl wat Tamwīl (BMT) Pesantren di Indonesia - Atika Rukminastiti Masrifah (Islamic Economics Journal, 2020)
Pesantren and Baitul Māl Wa Tamwīl (BMT) are not seemingly equal things to compare. The first focuses on spiritual and religious education, while the latter concentrates on the economic and financial activities. Nevertheless, Pesantrens have been considering the significance of economic development and empowerment, through a micro-finance institution. Hence, the analysis of its performance, in particular, the efficiency level is inevitable. This paper attempts to analyze the technical efficiency (including pure technical and scale efficiencies) of some Pesantren BMTs by using Data Envelopment Analysis (DEA). Additionally, this article also analyses the role of Pesantren BMTs for developing Micro-Entreprises (MEs), as well as toanalyse the roles of Pesantren BMT in ME’s wealth management. The results show that: first, generally, the efficiency of Pesantren BMTs is relatively low. Scale efficiency also indicates that operating of BMTs are still far from the optimal scale. Moreover, the average technical efficiencies (TE), scale efficiency (SE), and pure technical efficiency (PTE) of Pesantren BMTs in terms of intermediation have always been higher than those in terms of production. The possible improvements for inefficient Pesantren BMTs include increasing debitors (Y1) and total financing (Y2). They have to always been struggling to collect sizeable depositors, especially MEs, as well as total financing as their main purpose to empower them and enhance their economic development. The other possible improvements are to increase the collection (X4) and the distribution funds of ZISWAF (Y3). This result suggests that most Pesantren BMTs still focus on baitut tamwīl activities, extending financing as their main business. While the future, BMTs should play a more active role in baitul māl activities as their primary business. Second, Pesantren BMTs are useful for developing MEs and contribute a tremendous social benefit to society in several ways. Although the efficiency of BMTs is relatively low since generally, BMTs have achieved both profit and social benefit. Therefore, Islamic financing might be an appropriate model for MEs.